Risk of Acute Liver Injury in Agomelatine and Other Antidepressant Users in Four European Countries: A Cohort and Nested Case–Control Study Using Automated Health Data Sources - Pladevall-Vila, Manel; Pottegård, Anton; Schink, Tania; Reutfors, Johan; Morros, Rosa; Poblador-Plou, Beatriz; Timmer, Antje; Forns, Joan; Hellfritzsch, Maja; Reinders, Tammo; Hägg, David; Giner-Soriano, Maria; et al. (CNS drugs, 2019)
Background Agomelatine is a melatonin receptor agonist and serotonin 5-HT 2C receptor antagonist indicated for depression in adults. Hepatotoxic reactions like acute liver injury (ALI) are an identified risk in the European risk management plan for agomelatine. Hepatotoxic reactions have been reported for other antidepressants, but population studies quantifying these risks are scarce. Antidepressants are widely prescribed, and users often have risk factors for ALI (e.g. metabolic syndrome). Objective The goal was to estimate the risk of ALI associated with agomelatine and other antidepressants (fluoxetine, paroxetine, sertraline, escitalopram, mirtazapine, venlafaxine, duloxetine, and amitriptyline) when compared with citalopram in routine clinical practice. Method A nested case–control study was conducted using data sources in Denmark, Germany, Spain, and Sweden (study period 2009–2014). Three ALI endpoints were defined using International Classification of Diseases (ICD) codes: primary (specific codes) and secondary (all codes) endpoints used only hospital discharge codes; the tertiary endpoint included both inpatient and outpatient settings (all codes). Validation of endpoints was implemented. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for current use were estimated for each data source and combined. Results We evaluated 3,238,495 new antidepressant and 74,440 agomelatine users. For the primary endpoint, the OR for agomelatine versus citalopram was 0.48 (CI 0.13–1.71). Results were also < 1 when no exclusion criteria were applied (OR 0.37; CI 0.19–0.74), when all exclusion criteria except alcohol and drug abuse were applied (OR 0.47; CI 0.20–1.07), and for the secondary (OR 0.40; CI 0.05–3.11) and tertiary (OR 0.79; CI 0.50–1.25) endpoints. Regarding other antidepressants versus citalopram, most OR point estimates were also below one, although with varying widths of the 95% CIs. The result of the tertiary endpoint and the sensitivity analyses of the primary endpoint were the most precise. Conclusion In this study, using citalopram as a comparator, agomelatine was not associated with an increased risk of ALI hospitalisation. The results for agomelatine should be interpreted in the context of the European risk minimisation measures in place. Those measures may have induced selective prescribing and could explain the lower risk of ALI for agomelatine when compared with citalopram. Most other antidepressants evaluated had ORs suggesting a lower risk than citalopram, but additional studies are required to confirm or refute these results.